THE VALUE AND APPLICATION OF IMPROVISATION IN DANCE CHOREOGRAPHY TRAINING - XinYi, Song (E-Journal VFU, 2025)
As the core of dance art creation, dance choreography training has long sought a balance between "technique instruction" and "inspiration." Traditional choreography teaching often focuses on accumulating movement materials and training structural methods, while neglecting to some extent the deep stimulation of the creator's inner subjectivity and originality. Improvisation, as a method of instant artistic creation using the body as a medium under specific rules, is increasingly becoming an indispensable key link in modern and contemporary dance choreography training. This article aims to explore the multiple values of improvisation in dance choreography training, including stimulating the origin of movement, cultivating the choreographer's subjective consciousness, expanding creative thinking, and as a specific choreography method. It further elaborates on its specific application paths in teaching practice, aiming to demonstrate that improvisation is an important bridge connecting technique, thinking, and works, cultivating innovative choreography talents with independent artistic personalities.
Keywords: Improvisation; Dance Choreography; Training Value; Teaching Methods; Creative Thinking